Red River [videorecording (DVD)] - Wayne, John, 1907-1979; Clift, Montgomery; Dru, Joanne, 1923-1996; Chase, Borden; Bogdanovich, Peter, 1939- (Criterion collection, 2014)
With no market for his herd, the master of a vast cattle ranch and his son decide to head the first cattle drive over the now famous Chisholm Trail, past the Red River, into Missouri. The path is filled with hardship and the drive looks hopeless as the men struggle to prevail.